Confirm that the imaginary number i is a closed field - Ling Xie (Annals of Mathematics and Physics - Peertechz Publications, 2023)
In the History of mathematics of mankind, some strange symbols appeared when dealing with some mathematical problems, which were defined as imaginary numbers by mankind. The imaginary number has been idle for a long time since it was discovered. Later, mathematicians such as Gauss moved the imaginary number to the mathematical plane (Complex plane). Humans have also learned the difference between imaginary and real numbers, and have obtained the difference between the two types of numbers on the square root. My contribution is to discover the inconsistency between real and imaginary numbers. I have discovered a new method of calculating imaginary number logic that is deeply hidden. 2020 Mathematics Subject Classification: 03G27, 03F07, 03D45, 11U09, 08A05, 08A40.